ASSOCIAÇÃO ENTRE FUNÇÃO COGNITIVA E ATIVIDADES MOTORAS GROSSAS DE CRIANÇAS COM TRANSTORNO DO ESPECTRO AUTISTA (Movimenta (ISSN 1984-4298), 2022)
Objective: To explore the association between cognitive function and gross motor activities in children with autism spectrum disorder (ASD). Methods: An exploratory cross-sectional observational study was carried out with children aged between 5 and 12 years who were in rehabilitation. The Mini-Mental State Examination (MMSE) was used to screen cognitive function and to assess gross motor activities, dimensions D and E of the Gross Motor Function Measure (GMFM-88) were used. Simple regression analysis was performed between the MMSE total score and the GMFM-88 dimension D and E scores and the effect size (f) was calculated. Results: Thirty-three children were evaluated and the MMSE score was significantly associated and able to explain 49% of the GMFM D dimension score variability (p=0.0001; f=0.96) and 58% of the GMFM score variability. dimension E of the GMFM (p=0.0001; f=1.38). Conclusion: Cognitive function showed a strong association and was able to explain motor activity outcomes in children with ASD between 5 and 10 years of age. These findings may contribute to the knowledge of important aspects to be considered in the evaluation and therapeutic planning of the rehabilitation process of children with ASD.